Daily Context for Abusive and Neglectful Behavior in Family Caregiving for Dementia. (19th August 2019) - Pickering, Carolyn E Z; Yefimova, Maria; Maxwell, Christopher; Puga, Frank; Sullivan, Tami
Abstract: Background and Objectives: The purpose of this study was to identify risk and protective factors for abusive and neglectful behavior in the context of daily caregiving. Research Design and Methods: Family caregivers who co-reside with a care recipient with Alzheimer's disease and related dementia, recruited from social media, completed 21-days of diaries. Multilevel modeling with days ( n = 831) nested within caregivers ( N = 50) was used to evaluate relationships between hypothesized risk and protective factors and the odds of an abusive or neglectful behavior on a given day. Results: Disruptions in the daily routine and stress of the caregiver related to behavioral symptoms of the care recipient are significant risk factors for abusive and neglectful behavior. Participating in a meaningful activity with the care recipient when it occurs twice in a day is a significant protective factor against use of a neglect behavior (OR = 0.19; CI 0.06–0.64; p = .01), but not for abusive behavior. Hypotheses that spending the full day together would increase risk, and that receipt of instrumental support and caregiver participation in self-care would decrease risk, were not supported. Discussion and Implications: Findings demonstrate that risk of an abusive or neglectful behavior varies from day-to-day in the presence and absence of contextual factors, and that the majority of the variance in the odds an abusive or neglectful behavior occurring is related to day-level factors. Findings demonstrate that diary surveys are critical to identifying ecologically valid modifiable risk and protective factors for abusive and neglectful behaviors that can be targeted in future interventions.